Microvascular decompression for intermediate nerve neuralgia: a case report and literature review - Wang, Kan; Li, Wenhao; Bo, Yujie; Li, Biao; Wan, Jinxin; Mu, Luyan; Song, Yuwen (Frontiers in Surgery, 2024)
Intermediate nerve neuralgia (INN) is a rare craniofacial pain syndrome. The diagnosis of INN is challenging because of the complex ear sensory innervation that results in a clinical overlap with both trigeminal neuralgia (TN) and glossopharyngeal neuralgia (GPN). A 76-year-old woman with a remarkable medical history presented with right otalgia and mandibular pain for 7 years. Neurological examination revealed a diminished sensation in the distribution of the intermediate nerve (IN). Magnetic resonance imaging demonstrated an impression of the anterior inferior cerebellar artery (AICA) on the facial–vestibulocochlear nerve complex (VII/VIII complex). The patient underwent microvascular decompression (MVD) after long-term oral medication. We confirmed that the responsible vessel was close to the VII/VIII complex and isolated the vessel under the microscope via a right-sided suboccipital retrosigmoid approach. The patient's otalgia and mandibular pain disappeared after the operation. There were no additional neurological deficits. In conclusion, MVD is a safe and feasible option for patients with INN who fail to respond to adequate pharmacotherapy.